An Unusual Mural Paintings at the Charola of the Convent of Tomar: Red Lakes and Organic Binders - Manhita, Ana (2016)
This work presents the results of the analysis of the organic materials (red lakes and binders) from the flesh tones, wings, and vests of the angels from the mural paintings from the Charola of the Convent of Tomar. Pyrolysis coupled to gas chromatography and mass spectrometry (Py-GC/MS) was selected for the identification of binders, and liquid chromatography coupled to diode array and MS detection (LC/DAD/MS) was used for the identification of lakes in the red paint layers